2004
DOI: 10.1136/adc.2003.040881
|View full text |Cite
|
Sign up to set email alerts
|

The use of interferon beta in relapsing-remitting multiple sclerosis

Abstract: The use of interferon beta-1a to treat multiple sclerosis in a child of 7 years of age is discussed. To date, there is only one other published report of the use of interferon beta in a child as young as this. One year after commencing treatment she had shown significant clinical improvement, with a marked reduction in number of relapses. In her second year of treatment she suffered a major relapse from which she slowly recovered.M ultiple sclerosis (MS) is a chronic inflammatory disease of the central nervous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Safety and tolerability of IFNb and GA have been explored in several retrospective reviews. 29,[76][77][78][79][80][81][82][83]…”
Section: Immunomodulatory Therapiesmentioning
confidence: 99%
“…Safety and tolerability of IFNb and GA have been explored in several retrospective reviews. 29,[76][77][78][79][80][81][82][83]…”
Section: Immunomodulatory Therapiesmentioning
confidence: 99%
“…Small cohort studies and isolated case reports indicate that interferon-b therapies are well tolerated and appear to be effective in the treatment of pediatric multiple sclerosis. [19][20][21][22][23][24][25][26][27][28] To capture more comprehensive experience with subcutaneous interferon b-1a in a large, multinational pediatric multiple sclerosis population, this study reviewed the safety and tolerability of subcutaneous interferon b-1a in children and adolescents with demyelinating events, based on retrospective data from medical records. Although the study was not designed to evaluate efficacy, additional data were collected to explore the impact of treatment on clinical relapses.…”
mentioning
confidence: 99%
“…Still, it remains unclear how pediatric patients with MS respond to DMTs and whether regional differences impact the management of MS with DMTs. Small studies (most involving 50 or fewer participants) have demonstrated that baseline relapse rates decrease after treatment with DMTs [4][5][6][7][8][9][10][11][12]. Recently, our group, the REPLAY study investigators, completed the largest reported retrospective analysis of treatment experience with subcutaneous (sc) interferon (IFN) β-1a in pediatric patients with MS. Based on the review of medical records from 307 pediatric patients (298 of whom had a final diagnosis of MS) enrolled from eight countries, we found that adult doses of sc IFN β-1a (44 and 22 μg three times weekly [tiw]) were well tolerated and associated with a reduction in relapse rates compared with rates before treatment [12].…”
Section: Introductionmentioning
confidence: 99%